Radioprotection of Sensitive Rat Tissues by Oligoelements Se, Zn, Mn Plus Lachesis Muta Venom - Crescenti, Ernesto J. V. (2011)
In this study we first evaluated the general radioprotective efficacy of Se, Zn and Mn (4 μg/ml each) plus Lachesis muta venom (4 ng/ml) combination (O-LM) by determining survival on rats irradiated with lethal doses of gamma-rays. The aim of the second part of the study was to investigate the O-LM ability to prevent ionizing radiation-induced damage on small intestine, bone marrow and submandibular glands. Hence, histological characteristics and functional studies, together with proliferation and apoptotic marker levels on whole body irradiated rats with a 5 Gy dose were evaluated. Results show that all animals of the untreated group died after whole body irradiation with 8 and 10 Gy while 60 day-survival was more than 80% and 40% in O-LM-treated animals, respectively. Histopathological examinations revealed a high degree of small intestine and submandibular gland radioprotection 3 days post-irradiation. O-LM inhibited histological damage on small intestine, restoring the radiation-induced reduction in villous height and crypt number. O-LM prevented radiation-induced loss of salivary gland function and morphological alterations. These effects were associated to a complete inhibition of radiation-induced apoptosis. Furthermore, studies performed 30 days post-irradiation revealed that O-LM significantly improved bone marrow repopulation, increasing all medullar progenies to the extent of the non-irradiated animals, and completely prevented permanent submandibular gland alterations. Based on the present results and taking into account that O-LM is being safely administered in phase I clinical trial as an immunomodulator, we conclude that O-LM is a non-toxic promising approach to achieve radioprotection for patients undergoing radiotherapy.